Follow-up of Favipiravir-Induced Nail Fluorescence: Implications for Nail and Drugs - Hüsna Güder; Zeynep Güneş Özünal (Mattioli1885, 2023)
Introduction: Favipiravir creates fluorescence on nails, which can be seen with Wood's light. Objectives: The objectives of this study are to examine the properties of fluorescence in the nail due to favipiravir and to observe whether other drugs also produce fluorescence in the nail. Methods: The research is descriptive, prospective, and quantitative. This study recruited 30 healthcare workers who received favipiravir treatment and 30 volunteers who took or did not take any medication except favipiravir from March 2021 to December 2021. Fingernails of the patients and control groups were examined under Wood's light in the darkroom. If fluorescence was observed in the fingernails, we followed up once a month until the fluorescence disappeared. We calculated the nail growth rate by dividing the distance of nail fluorescence from the proximal nail fold by the number of days since favipiravir was started. Results: We found nail fluorescence in all patients receiving a loading dose of favipiravir. The fluorescence in the nail decreased and disappeared in the 3rd month. The average nail growth rate at the first visit was 0.14 mm/day. The nail growth rate at the second visit was 0.10 mm/day. A statistically significant difference was found between the first and second visit nail growth rates (z: -2.576; p=0.010<0.05). We found that other drugs did not produce any fluorescence in the nail. Conclusions: Nail fluorescence induced by favipiravir is dose-dependent and decreases in intensity over time. Nail fluorescence due to favipiravir is likely due to the active ingredient of the drug.